Evaluation Model for Emergency Material Suppliers in Emergency Logistics Systems Based on Game Theory–TOPSIS Method - Lihao Lei; Songtao Yu; Yuxian Ke; Linhong Deng; Qian Kang (Systems)
Emergency material suppliers serve as a critical component within emergency logistics systems, with their capabilities directly influencing operational efficiency. To identify suppliers with comprehensive capabilities, this study establishes an evaluation index system encompassing four key dimensions: emergency resilience, logistics costs, material quality, and supplier internal conditions. The methodology integrates subjective weights derived from the G1 method and objective weights calculated by entropy weighting, subsequently employing game theory to reconcile conflicts between weighting methods and determine comprehensive weights. The TOPSIS method is applied to identify optimal suppliers through relative approximation comparisons. A case study demonstrates the model’s effectiveness, with comparative analysis against AHP and traditional combination weighting methods revealing distinct advantages: under information distortion conditions, the game theory combination weighting exhibits significantly lower weight fluctuations (0.00018) compared to the additive synthesis (0.00044) and multiplicative synthesis methods (0.000503). This evidence confirms that game theory not only demonstrates superior stability and adaptability for emergency evaluations but also effectively balances weight conflicts, yielding more rational assessment outcomes. The research findings validate the practical utility of this game theory–TOPSIS integrated evaluation model, providing valuable decision support for emergency management professionals.